Inside Cover: Strain‐Promoted Cycloaddition of Cyclopropenes with o‐Quinones: A Rapid Click Reaction (Angew. Chem. Int. Ed. 32/2018). Issue 32 (14th June 2018) - Gahtory, Digvijay; Sen, Rickdeb; Kuzmyn, Andriy R.; Escorihuela, Jorge; Zuilhof, Han
Abstract : Small is beautiful when it comes to click reactions. In their Communication onpage 10118 ff., H. Zuilhof et al. report the reaction between a strained alkene and an o ‐quinone, and the high yield thereof in both solution‐phase and surface‐bound reactions. Subsequently, they show that this Diels–Alder reaction outperforms faster reactions under sterically confined conditions, indicating that the cyclopropene dienophile is the highly favored reagent because of its small size.